Interpersonal communication approach in addressing TB stigma in Bandung City - Solihin, Olih; Lubis, Djuara Pangihutan; Muljono, Pudji; Amanah, Siti (Jurnal Kajian Komunikasi, 2024)
Background: Tuberculosis (TB) patients face medical challenges and stigmatization from their surroundings. The Terjang Foundation is actively working to combat societal stigma towards TB patients. Purpose: This research analyzes the Terjang Foundation’s interpersonal communication approach to combating stigma towards TB patients. By understanding and assessing the communication methods employed by the foundation, the study aims to contribute to developing effective strategies for reducing the negative stigma associated with TB. Methods: This research utilizes a qualitative research method with a case study approach. In-depth interviews, field observations, and literature reviews are conducted to gather relevant data and insights. Results: The results of this study indicate that the Terjang Foundation employs five positive attitudes in their interpersonal communication approach to combat stigma towards TB patients: openness, empathy, positivity, equality, and supportiveness. These attitudes contribute to fostering an environment that challenges the negative stigma associated with TB. Continuous and frequent communication is crucial in combating stigma, promoting understanding and empathy, and disseminating accurate information. Empathy and equality emerge as prominent positive attitudes consistently demonstrated in communication. Conclusion: The study concludes that maintaining an ongoing and frequent communication process is essential for combating stigma in interpersonal communication efforts. Implications: The research findings have both practical and theoretical implications. Practically, the study emphasizes the importance of adopting positive attitudes, such as empathy and equality, in interpersonal communication strategies to reduce stigma towards TB patients. These insights can guide organizations, healthcare providers, and policymakers in developing effective communication campaigns and interventions to combat stigma related to TB and other diseases.